2020
DOI: 10.3168/jds.2019-17071
|View full text |Cite
|
Sign up to set email alerts
|

Widespread basal cytochrome P450 expression in extrahepatic bovine tissues and isolated cells

Abstract: Periparturient cattle face increased risk of both metabolic and infectious diseases. Factors contributing to this predisposition include oxidized polyunsaturated fatty acids, also known as oxylipids, whose production is altered during the periparturient period and in diseased cattle. Alterations in the production of oxylipids derived from cytochrome P450 (CYP450) enzymes are over-represented during times of increased disease risk and clinical disease, such as mastitis. Many of these same CYP450 enzymes additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…An additional unique and advantageous characteristic of BMEC to model the effects of vitamin E analogs is a lack of measurable CYP4F2 transcript expression (Kuhn et al, 2020). The cytochrome P450 family 4 subfamily F member 2 enzyme (CYP4F2), is thought to be the sole enzyme responsible for the breakdown of vitamin E analogs and has a preference for metabolizing non-α-tocopherol analogs of vitamin E Parker, 2002, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…An additional unique and advantageous characteristic of BMEC to model the effects of vitamin E analogs is a lack of measurable CYP4F2 transcript expression (Kuhn et al, 2020). The cytochrome P450 family 4 subfamily F member 2 enzyme (CYP4F2), is thought to be the sole enzyme responsible for the breakdown of vitamin E analogs and has a preference for metabolizing non-α-tocopherol analogs of vitamin E Parker, 2002, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, experiments were additionally carried out in bovine microsomes from kidney and mammary tissues. Bovine renal tissue has the greatest CYP4F2 expression on an mRNA basis of any organ making it potentially an important contributor to systemic 20‐HETE production (Kuhn et al, 2020). Unlike the human CYP4F2 microsome preparations, whole organ bovine microsomes include most CYP450 present within a given tissue type, implying CYP4A11—a potentially considerable contributor to 20‐HETE production—is likely present and could dilute the inhibitory effects of vitamin E analogs on overall 20‐HETE concentrations (Powell et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In calves, the CYP4F2 mRNA level was the highest in the liver, followed by the testis, adrenal gland, duodenum, and jejunum, which have high α-Toc accumulation [35]. The CYP4F2 mRNA in lactating Holstein cows was significantly higher in the kidney than in the liver, lung, mammary gland, heart, skeletal muscle, spleen and uterus [38]. Furthermore, the hepatic [2,55] and mammary [2] CYP4F2 mRNA expression in transition dairy cows was investigated (described in Section 4).…”
Section: Atp-binding Cassette Transporter A1mentioning
confidence: 95%
“…In the last 10 years, several studies have shown evidence that the ovine [33,34] and bovine [35] liver may play an important role in the regulation of VE disposition because of the high expression of VE-related molecules. In addition, other peripheral tissues showed unique expression patterns for VE-related molecules and VE accumulation properties in cattle [2,[35][36][37][38]. These findings indicate that the expression of VE-related genes in the liver and non-hepatic tissues may be involved in the regulation of VE status in cows.…”
Section: Introductionmentioning
confidence: 99%